PENGARUH ASAP CAIR TEMPURUNG KELAPA PADA PLAK INDEX - Wiworo Haryani (Jurnal Kesehatan Gigi, 2018)
TITLETHE INFLUENCE OF SMOKE LIQUID OF COCONUT SHELL ON PLAQUE INDEXABSTRACTCoconut shell contains high antioxidant an anti bacterial agent which could influence oral bacterial growth in dental plaque. The extract – known as liquid smoke – is the vinegar of biomass pyrolysis process. This study wanted to know the influence of mouth rinsing using liquid smoke of coconut shell toward dental plaque’s existence.This study was used the quasi-experiment method. The design of this study was a pre-post the  experiment. The samples were randomized on JKG’s students which were 24 students. The data were analyzed Anova Test.The result showed that there wasa significant influence before and after mouth rinsing with liquid smoke (p-value 0.017; 0.001; 0.000 0.005) in each group. The increase of the concentration of liquid smoke had a significant influence on the decrease of plaque index (p-value 0.015 0.005). It’s suggested that this research had to be continued to find out the influence of the concentrations of smoke liquid on oral bacteria.